Advances in the Understanding, Diagnosis, and Treatment of Systemic Sclerosis A Comprehensive Review of Recent Developments - Moreau, Igor; Kulak, Maria; Sokołowska, Katarzyna; Bereza, Dawid; Polańska, Paulina; Lang, Miriam; Woch, Barbara (Journal of Education, Health and Sport, 2024)
Systemic sclerosis (SSc) is a multifaceted autoimmune disorder characterized by widespread organ involvement, impacting the skin, lungs, gastrointestinal tract, and blood vessels. Patients often confront a reduced lifespan, primarily attributed to pulmonary complications. Current therapeutic strategies concentrate on organ-specific interventions to mitigate inflammation and alleviate symptoms. Immunosuppressive drugs, vasodilators, and anti-fibrotic agents are commonly employed, but ongoing research explores novel drugs and therapeutic approaches. Autologous stem cell transplantation is considered in rapidly progressing interstitial lung disease, although potential complications must be carefully weighed. Recent studies delve into the intricate pathogenesis of SSc, revealing abnormalities in metabolic pathways and protein regulation. The disease manifests with diverse symptoms affecting various organs, with vascular involvement significantly contributing to morbidity, especially pulmonary arterial hypertension. Complications, including heightened susceptibility to infections, are exacerbated by the disease and its treatments. Ongoing research investigates potential treatments such as GPR68 antagonists, soluble guanylate cyclase activators, and melanocortin 1 receptor agonists, displaying promising results in improving pulmonary function. Multiple clinical trials for various drugs are currently underway. In conclusion, addressing the complexities of systemic sclerosis requires a multidisciplinary approach. Understanding its intricate pathogenesis and developing targeted therapies are pivotal for enhancing patient outcomes and extending survival.